Pemberdayaan Ibu PKK dalam Meningkatkan Kemandirian Ekonomi Keluarga di Era Digital - Rismawati; Nur Syifa Syaharany; Santi Aprilianti; Wanda Septianawati (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
Empowerment of PKK (Family Welfare Empowerment) mothers plays an important role in increasing family economic independence, especially in today's digital era. This study aims to analyze the role and empowerment strategies of PKK mothers in utilizing digital technology to increase family income. With access to technology and digital entrepreneurship training, PKK mothers can develop home businesses, improve digital marketing skills, and expand market reach. The research method used is a qualitative method, with data collection through interviews and observations of PKK mothers' groups in various regions. The results of the study show that the use of digital technology, such as social media and e-commerce platforms, significantly contributes to increasing family income and economic independence. Obstacles faced in this empowerment include limited access to technology, digital literacy, and capital support. This study concludes that a structured and sustainable digital-based empowerment program can be an effective solution in increasing family welfare and economic independence through the active role of PKK mothers.